Public-Key Encryption In The Standard Model Against Strong Leakage Adversary. (3rd June 2020) - Alawatugoda, Janaka
Abstract: Over the years, security against adaptively chosen-ciphertext attacks (CCA2) is considered as the strongest security definition for public-key encryption schemes. With the uprise of side-channel attacks, new security definitions are proposed, addressing leakage of secret keys together with the standard CCA2 definition. Among the new security definitions, security against continuous and after-the-fact leakage-resilient CCA2 can be considered as the strongest security definition, which is called as security against (continuous) adaptively chosen-ciphertext leakage attacks (continuous CCLA2). In this paper, we present a construction of a public-key encryption scheme, namely LR-PKE, which satisfies the aforementioned security definition. The security of our public-key encryption scheme is proven in the standard model, under decision BDH assumption. Thus, we emphasize that our public-key encryption scheme LR-PKE is (continuous) CCLA2-secure in the standard model. For our construction of LR-PKE, we have used a strong one-time signature scheme and a leakage-resilient refreshing protocol as underlying building blocks. The leakage bound is $0.15n\log p -1$ bits per leakage query, for a security parameter $k$ and a statistical security parameter $n$, such that $\log p ≥ k$ and $n$ is a function of $k$ . It is possible to see that LR-PKE is efficient enough to be used for real-world usage.